2012
DOI: 10.1371/journal.pone.0038918
|View full text |Cite
|
Sign up to set email alerts
|

The -2518A/G Polymorphism in the MCP-1 Gene and Tuberculosis Risk: A Meta-Analysis

Abstract: BackgroundThe -2518A/G polymorphism in the monocyte chemoattractant protein-1 (MCP-1) gene has been implicated in the susceptibility to tuberculosis (TB), but the results are not conclusive. The aim of this study is to investigate the association between the -2518A/G polymorphism in the MCP-1 gene and the risk of tuberculosis by meta-analysis.MethodsWe searched Pubmed, Embase, CNKI and Wanfang databases, covering all studies until April 29th, 2011. Statistical analyses were performed using the Revman4.2 and ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…There were 3 previous meta-analyses that evaluated the association between the MCP-1 -2518A/G polymorphism and TB susceptibility (Feng et al, 2011;Zhang et al, 2012;Gong et al, 2013). Compared with these reports, ours revealed some new insights.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…There were 3 previous meta-analyses that evaluated the association between the MCP-1 -2518A/G polymorphism and TB susceptibility (Feng et al, 2011;Zhang et al, 2012;Gong et al, 2013). Compared with these reports, ours revealed some new insights.…”
Section: Discussionmentioning
confidence: 68%
“…Zhang et al (2012) showed that significantly elevated risks were observed in Asians and Latinos, but not in Africans between the -2518A/G polymorphism in the MCP-1 gene and TB. Another group reported that the CCL2-2518G allele increased the risk of developing TB in Asians and Hispanics (Feng et al, 2012).…”
Section: Tuberculosis (Tb) Is An Infectious Disease Caused By the Bacmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, meta‐analysis studies revealed that the MCP‐1‐2518G allele increased the risk of developing TB for Asians and Hispanics, but not for Africans (Feng et al., ; Tian et al., ; Zhang et al., ). More recently, these data have been well supported by the Vásquez‐Loarte meta‐analysis study; however, the authors stressed that this genetic analysis results were influenced significantly by the ethnicity of the study's subjects, as the MCP‐1‐ 2518G allele may not be associated with some Asian groups, such as those from India and Persia (Vásquez‐Loarte, Trubnykova, & Guio, ).…”
Section: Candidate Genes and The Risk Of Developing Tbmentioning
confidence: 99%
“…2 A 2014 World Health Organization report estimated that even though there are so many people infected with MTB, only one-third of the global population has been latently infected without clinical symptoms, and about 10% of infected individuals develop into active PTB during their lifetime. 3 Apart from bacterial variability, genetic host factors may also play a crucial role in an individual's predisposition to PTB. 4 Stead and others reported that individuals with African ancestry were twice as likely to be infected with MTB as individuals with European ancestry, even though they shared the same environment.…”
Section: Introductionmentioning
confidence: 99%